(untitled) (The Pretoria Student Law Review, 2021)
The COVID-19 pandemic provided ideal conditions for the violation of human rights. In efforts to curb the spread of the virus, numerous states violated their international law obligations outlined in treaties and customary international law. This article aims to analyse state responses to the global pandemic and will consider how their lawfulness should be measured. To this end, the framework of due diligence is utilised as a system to regulate and assess the legality of state actions amidst times of emergency. Furthermore, this article argues that the principle of due diligence must be developed to sufficiently regulate instances of derogation that extend beyond restrictions. This development must also be informed by an intersectional approach that prioritises the protection of vulnerable groups, owing to the disproportionate impact of COVID-19 on these communities. Stemming from this analysis, the article will conclude by considering the landscape of state actions in handling COVID-19 under the banner of due diligence and imagines a construction of international law that more adequately protects human rights amid regional and global crises.